613 Microsurgical Salvage of Neonatal Upper Limb Ischaemia Subsequent to Intrauterine Brachial Vessel Constriction. (4th May 2021) - Clements, J; McBride, M; Fogarty, B; Lewis, H
Abstract: Introduction: We report a case of limb salvage due to intra uterine brachial artery thrombosis. Treatment modalities include medical, endovascular, and surgical. Early recognition, prompt institution of appropriate treatment and monitoring is vital to achieve successful revascularisation and prevention of lifelong morbidity. Description: A male baby at (36 + 6week) gestation was born to a nulliparous mother with gestational diabetes via uncomplicated elective caesarean section. The child was noted to have a 'flail' ischeamic limb post-delivery. There were no palpable pulses in the limb and ultrasonography confirmed thrombosis of the proximal brachial artery. Aetiology was due to dense fibrotic circumferential constriction of the brachial vessels and plexus. Successful revascularisation was achieved with a contralateral interposition reversed great saphenous vein graft. Discussion: Neonatal limb ischaemia is a rare disease entity with devastating morbidity- including compartment syndrome, tissue loss, limb loss, reduced limb growth, irreparable neuropathies and Volkmann's syndrome. The initial diagnosis is based on the characteristic sequelae of ischaemia. Therapy should be individualised based on the clinical presentation. Early recognition, prompt institution of appropriate treatment and monitoring is vital to achieve successful revascularisation and prevention of lifelong morbidity.